1999
DOI: 10.1038/sj.onc.1202886
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity and expression of the early adenovirus proteins are important regulators of wild-type and ΔE1B adenovirus replication in human cells

Abstract: An adenovirus mutant lacking the expression of the large E1B protein (DE1B) has been reported to replicate selectively in cells lacking the expression of functionally wild-type (wt) p53. Based on these results the DE1B or ONYX-015 virus has been proposed to be an oncolytic virus which might be useful to treat p53-de®cient tumors. Recently however, contradictory results have been published indicating that p53-dependent cell death is required for productive adenovirus infection. Since there is an urgent need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
16
3
Order By: Relevance
“…The results clearly indicate that the endogenous E1a promoter in the E1B55K-deleted virus is more activated in Hep3B cells than that in Saos2 cells. Unlike the data reported by Steegenga, 34 we showed that Hep3B and Saos2 cells could be equally infected by adenoviruses (Figure 1c). This conclusion was further verified by comparing the viral DNA uptake between the two cell lines after dl1520/ÀE2a infection.…”
Section: The E1a Promoter Was Activated In Hep3b Cells But Restrictedcontrasting
confidence: 99%
See 4 more Smart Citations
“…The results clearly indicate that the endogenous E1a promoter in the E1B55K-deleted virus is more activated in Hep3B cells than that in Saos2 cells. Unlike the data reported by Steegenga, 34 we showed that Hep3B and Saos2 cells could be equally infected by adenoviruses (Figure 1c). This conclusion was further verified by comparing the viral DNA uptake between the two cell lines after dl1520/ÀE2a infection.…”
Section: The E1a Promoter Was Activated In Hep3b Cells But Restrictedcontrasting
confidence: 99%
“…At 2 days after infection, cells were observed for CPE that were characterized by unattached and rounded-up cells. Similar to the data reported by Steegenga et al, 34 CPE were observed in Hep3B cancer cells infected with dl1520 but not in the Saos2 cells (Figure 2). In fact, all the viruses can destroy Hep3B cells.…”
Section: E1a Expression Levels Affect the Cpe Of E1b55k-deleted Adenosupporting
confidence: 90%
See 3 more Smart Citations